2021
DOI: 10.1111/1346-8138.16058
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal heavy metal exposure, total immunoglobulin E, trajectory, and atopic diseases: A 15‐year follow‐up study of a Taiwanese birth cohort

Abstract: Prenatal exposure to heavy metals may cause atopic diseases. Little association between cord blood total immunoglobulin E (CB‐tIgE) levels and the occurrence of atopic diseases has been found. This study investigated the atopic status and tIgE trajectory trend in a Taiwanese birth cohort over 15 years. We also assessed the effect of maternal heavy metal exposure on maternal serum cytokine and CB‐tIgE levels. We recruited 430 pregnant women during their third trimester in 2000–2001. Maternal urinary heavy metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 30 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…Our previous study showed that the maternal urinary arsenic concentration was associated with a significant risk of increased cord blood immunoglobulin E (IgE) levels >1 IU/mL (odds ration [OR] 1.845). 9 Among the heavy metals we tested in the maternal urine (arsenic, iron, Ni, cadmium, and lead), we found that the maternal Ni exposure is selectively associated with increased maternal IL-2 and IL-6 serum levels but not with the maternal or cord blood IgE. Hence, we sought to determine whether maternal Ni exposure affects the development of atopic dermatitis and immune abnormalities in their children.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study showed that the maternal urinary arsenic concentration was associated with a significant risk of increased cord blood immunoglobulin E (IgE) levels >1 IU/mL (odds ration [OR] 1.845). 9 Among the heavy metals we tested in the maternal urine (arsenic, iron, Ni, cadmium, and lead), we found that the maternal Ni exposure is selectively associated with increased maternal IL-2 and IL-6 serum levels but not with the maternal or cord blood IgE. Hence, we sought to determine whether maternal Ni exposure affects the development of atopic dermatitis and immune abnormalities in their children.…”
Section: Introductionmentioning
confidence: 99%